Moderation of prior exposure to trauma on the inverse relationship between callous-unemotional traits and amygdala responses to fearful expressions: an exploratory study. Issue 15 (12th February 2018) - Meffert, Harma; Thornton, Laura C.; Tyler, Patrick M.; Botkin, Mary L.; Erway, Anna K.; Kolli, Venkata; Pope, Kayla; White, Stuart F.; Blair, R. James R.
Abstract: Background: Previous work has shown that amygdala responsiveness to fearful expressions is inversely related to level of callous-unemotional (CU) traits (i.e. reduced guilt and empathy) in youth with conduct problems. However, some research has suggested that the relationship between pathophysiology and CU traits may be different in those youth with significant prior trauma exposure. Methods: In experiment 1, 72 youth with varying levels of disruptive behavior and trauma exposure performed a gender discrimination task while viewing morphed fear expressions (0, 50, 100, 150 fear) and Blood Oxygenation Level Dependent responses were recorded. In experiment 2, 66 of these youth performed the Social Goals Task, which measures self-reports of the importance of specific social goals to the participant in provoking social situations. Results: In experiment 1, a significant CU traits-by-trauma exposure interaction was observed within right amygdala; fear intensity-modulated amygdala responses negatively predicted CU traits for those youth with low levels of trauma but positively predicted CU traits for those with high levels of trauma. In experiment 2, a bootstrapped model revealed that the indirect effect of fear intensity amygdala response on social goal importance through CU traits is moderated by prior trauma exposure. Conclusions: This study, while exploratory, indicates that the pathophysiology associated with CU traits differs in youth as a function of prior trauma exposure. These data suggest that prior trauma exposure should be considered when evaluating potential interventions for youth with high CU traits.